Penyusunan Indeks Beranotasi dan Kliping Artikel dalam Majalah Tribrata News di Perpustakaan Kepolisian Daerah Sumatera Barat - Wahyuni, Fitri; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract The purpose of this study were to describe of making an annotated index and clipping of Tribrata News magazine articles in the Library of Police Regional West Sumatera and can be used to find information needed quickly and easily. The method used in this study is descriptive method. With data collection techniques through direct observation. In making an annotated index there are nine stage is: (1) collecting magazines; (2) the selection of magazines; (3) the selection of magazine articles; (4 )the creating clippings of magazine articles; (5) article description creation; (6) article annotation creation; (7) keyword determination ; (8)preparation of index of magazine articles; (9) typing of index of magazine article .Keywords: annotated index; article; magazine